Effects of exercise dose based on the ACSM recommendations on depression in hemodialysis patients: a systematic review and meta-analysis of randomized controlled trials - Fang, Yang; Xiaoling, Bai; Huan, Li; Yaping, Guan; Binying, Zhang; Man, Wang; Juan, Wu; Xinyu, Liu (Frontiers in Physiology, 2025)
ObjectiveTo explore the impact of various exercise doses on depressive symptoms among hemodialysis patients and offer valuable guidance for the selection of optimal exercise doses in clinical practice settings.MethodsA comprehensive systematic review was conducted across four major databases, namely, PubMed, Embase, Web of Science, and Cochrane Library, covering the period from their inception until August 2024. Exercise interventions were classified based on adherence to American College of Sports Medicine (ACSM) recommendations, dividing studies into groups with high and low/uncertain ACSM adherence. A meta-analysis was performed utilising Review Manager5.4.1 to assess the effects of ACSM adherence on depression in hemodialysis patients.ResultsThis meta-analysis incorporated a total of 19 randomized controlled trials, involving 1,285 patients. The mean age of the patients ranged from 33.2 to 70 years, and the average body mass index (BMI) fluctuated between 23.3 and 28.81 kg/m2. Males accounted for a relatively larger proportion of the participants. Among these trials, 14 were classified as having high ACSM adherence, while 5 were categorized as having low or uncertain adherence. Overall, exercise markedly improved depression in hemodialysis patients (SMD: −0.63, 95% CI: −0.87, −0.39; p < 0.05). The high ACSM adherence group showed greater improvement relative to the low/uncertain adherence group (SMD: −0.66 vs. −0.56). No notable disparities were noted in the effects of exercise duration or patient age on depression outcomes between the subgroups (p = 0.86, p = 0.48).ConclusionExercise interventions that exhibit high adherence to the ACSM guidelines prove to be more efficacious in alleviating depression among hemodialysis patients as compared to those with low or uncertain adherence levels.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/#myprospero